Embedding Sustainability Values in Fashion Education through Ready-to-Wear Design: A Feasibility Study of the ‘KONKA’ Collection - Dihya Reginia; Sita Nurmasitah (Jurnal Penelitian Pendidikan, 2026)
The fashion industry, driven by fast fashion practices, significantly contributes to textile waste, highlighting the need for sustainable approaches within fashion education. This study examines the feasibility of the KONKA sustainable ready-to-wear collection as a design-based learning medium for embedding sustainability values in fashion education. The KONKA collection applies upcycling techniques by transforming two discarded shirts into a single skirt design, with the traditional game of congklak serving as the primary source of design inspiration. A descriptive, quantitative method was employed, utilizing a percentage-based feasibility assessment. Data were collected through a design feasibility instrument and evaluated by three fashion design experts, focusing on color, design lines, silhouette, proportional balance, and center of interest. The results show that the KONKA design achieved a feasibility score of 95.6%, categorized as highly feasible. These findings suggest that upcycling-based ready-to-wear design can serve as an effective pedagogical medium for embedding sustainability values, resulting in designs that are both aesthetically pleasing and functionally practical, as well as culturally meaningful. This study supports Education for Sustainable Development (ESD) in fashion education, offering insights for curriculum development and sustainable fashion practices.